2016
DOI: 10.1038/srep19364
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Chemometrics and Quantum Mechanics Methods Applied to Analysis of Femtosecond Transient Absorption Spectrum of Ortho-Nitroaniline

Abstract: A combination of the advanced chemometrics method with quantum mechanics calculation was for the first time applied to explore a facile yet efficient analysis strategy to thoroughly resolve femtosecond transient absorption spectroscopy of ortho-nitroaniline (ONA), served as a model compound of important nitroaromatics and explosives. The result revealed that the ONA molecule is primarily excited to S3 excited state from the ground state and then ultrafast relaxes to S2 state. The internal conversion from S2 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…Tables S4 and S5 contain the excited state energies and oscillator strengths for ONA + at the S 0 and D 0 geometries, respectively; only the EOM-CCSD results are shown. Although no calculations of ONA + excited states have been reported to the best of our knowledge, our calculated energy for the neutral ONA S 1 state of 3.79 eV at the TD-CAM-B3LYP level is reasonably close to literature values for the S 1 energy of TATB (3.63 eV at the TD-B3LYP/6-311++G­(d,p) level) and ONA (3.06 eV at the same level in water) …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Tables S4 and S5 contain the excited state energies and oscillator strengths for ONA + at the S 0 and D 0 geometries, respectively; only the EOM-CCSD results are shown. Although no calculations of ONA + excited states have been reported to the best of our knowledge, our calculated energy for the neutral ONA S 1 state of 3.79 eV at the TD-CAM-B3LYP level is reasonably close to literature values for the S 1 energy of TATB (3.63 eV at the TD-B3LYP/6-311++G­(d,p) level) and ONA (3.06 eV at the same level in water) …”
Section: Resultssupporting
confidence: 86%
“…Although no calculations of ONA + excited states have been reported to the best of our knowledge, our calculated energy for the neutral ONA S 1 state of 3.79 eV at the TD-CAM-B3LYP level is reasonably close to literature values for the S 1 energy of TATB (3.63 eV at the TD-B3LYP/ 6-311++G(d,p) level) 10 and ONA (3.06 eV at the same level in water). 53 The results in Figure 2 show that ONA behaves quite differently from other related nitroaromatic molecules. Previous studies by our group showed that ortho-nitrotoluene, a closely related molecule to ONA, went from a C−NO 2 torsional angle of 26.0 to 35.5°upon ionization.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, we must analyse the transition according to the following information: rst, TATB is a photosensitive EM which undergoes colour changes from yellow to green or darker under light irradiation/photolysis, which has been attributed to the formation of a long-lived radical in the T 1 state; 22 and second, intersystem crossing to the T 1 state is likely to happen in this case. 29 On the basis of the foregoing arguments, it would be reasonable to assign the decay of the relaxed S 1 state to the S 1 / T 1 transition in this work. The Kohn-Sham orbitals, electron distribution, and orbital energies are in good agreement with this interpretation.…”
Section: Assignment Of the S 1 / T 1 Transition And De-excitation Promentioning
confidence: 87%
“…Moreover, these calculations do not consider direct dissociation from the triplet state, and additionally, the assignment of translational energy components based on a single classical trajectory may not be statistically valid . Theoretical and time-resolved experimental studies show that the motions localized on the nitro group are primarily responsible for the nonadiabatic dynamics in the excited electronic states of nitrobenzene and reveal that irrespective of the initial excitation energy, an ultrafast internal conversion followed by an intersystem crossing results in populating the T 1 state, which is invariant to the nature of substitution on the nitrobenzene. Lin and co-workers, based on the excitation energy dependence of the slow-to-fast ( s / f ) branching ratio, have surmised that the fast components appear due to direct dissociation from the T 1 state, while the slow component from the S 0 state, in concurrence with other experimental investigations. , In contrast, many theoretical reports suggest both the fast and slow translational energy components are due to a second intersystem crossing from T 1 to S 0 surface, , which is in accord with the time-resolved photoelectron measurements …”
mentioning
confidence: 99%
“…In this work, we examine, holistically, the trends in the branching ratio of slow-to-fast ( s / f ) translational energy components for the NO release obtained by a velocity map imaging technique following 266 nm photolysis of nitrobenzene and a series of ortho -substituted nitrobenzenes, viz., o -nitrotoluene, o -nitroanisole, o -nitroaniline, and o -nitrophenol. It has been reported that for nitrobenzene, o -nitrotoluene, o -nitroaniline, and o -nitrophenol time-resolved experiments following 266 nm excitation reveal ultrafast decay of the initially excited state to the T 1 state; however, the corresponding NO release experiments following 266 nm excitation for various ortho -nitrobenzenes, with the exception of nitrobenzene, are conspicuously missing. The experimental results are interpreted using DFT [B3LYP/6-311++g (d,p)] calculations, wherein it is proposed that the dynamics on the T 1 surface along the minimum energy path dictates the s / f branching ratio.…”
mentioning
confidence: 99%